Coevolution, diversification and alternative states in two‐trophic communities. (17th November 2020) - Northfield, Tobin D.; Ripa, Jörgen; Nell, Lucas A.; Ives, Anthony R.
Abstract: Single‐trait eco‐evolutionary models of arms races between consumers and their resource species often show inhibition rather than promotion of community diversification. In contrast, modelling arms races involving multiple traits, we found that arms races can promote diversification when trade‐off costs among traits make simultaneous investment in multiple traits either more beneficial or more costly. Coevolution between resource and consumer species generates an adaptive landscape for each, with the configuration giving predictable suites of consumer and resource species. Nonetheless, the adaptive landscape contains multiple alternative stable states, and which stable community is reached depends on small stochastic differences occurring along evolutionary pathways. Our results may solve a puzzling conflict between eco‐evolutionary theory that predicts community diversification via consumer–resource interactions will be rare, and empirical research that has uncovered real cases. Furthermore, our results suggest that these real cases might be just a subset of alternative stable communities. Abstract : Clone‐based model for two resource and consumer traits in a single community for 2 × 10 6 model iterations. Each point at a given time represents an individual clone that has the same phenotype (trait values), and a clone is assumed to terminate when its density drops below 0.0001. To identify the traits across the same groups of resource clones, after 0.2 × 10 6 iterations clones with final values of trait 1 (trait 2) less than 0.2 are coloured black (red) after trait divergence, and the remaining clones are coloured blue; a similar approach is used for consumer traits using a trait value threshold of 0.9.